Edukasi Konformitas Kelompok Bermain di Kalangan Siswa SMAN 6 Tangerang Untuk Mencegah Penyimpangan Perilaku - Vilya Dwi Agustini; Andys Tiara; Wininda Qusnul Khotimah (Prisani Cendekia, 2023)
Participating in groups is a fact of life. One of the tendencies of every human being is to live in groups, get involved int the other people’s life. The teenagers are no exception. Our partners in this activity is students of SMAN 6 Tangerang who are aged 16-17 years. This age is included in the Middle and Late Adolescent categories. Middle and late adolescence is the age where at this stage individuals really need friends and a period of consolidation towards the adult period so they tend to live in groups. However, it is unfortunate that partners didn’t get education related to something that can control their emotional self as a teenager who is prone to conflict, anxiety, and influence. One of them is the conformity of the play group and its influence on communication behavior. In the implementation of this activity, the method used by the team to handle the solution was in the form of education or counseling related to Group Conformity and Behavioral Deviations. This training is carried out through Zoom Meeting media. This activity goes succesfully, participants assessed that all the delivery of the material was understandable, participants were also able to know and understand well what group conformity is and its influence on communication behavior.